The Effect of Financing Risk and Efficiency Level on the Profitability of Islamic Commercial Banks in Indonesia (International Journal of Economics and Management Research, 2026)
This study examines the effect of financing risk and efficiency level on the profitability of Islamic commercial banks in Indonesia. The study employs a quantitative research design using secondary data from the annual financial statements of Islamic banks over a specified period. Financing risk is measured by the Non-Performing Financing (NPF) ratio, while efficiency level is measured using the Operating Expenses to Operating Income (BOPO) ratio. Profitability is represented by Return on Assets (ROA). Multiple linear regression analysis is used to test the hypotheses, after confirming that classical assumptions—including normality, multicollinearity, heteroscedasticity, and autocorrelation—are satisfied.The regression results indicate that financing risk negatively affects profitability, with a regression coefficient of approximately −0.412, a t-statistic of −3.05, and a p-value of 0.004, suggesting that higher NPF reduces bank profits. Efficiency level positively influences profitability, with a coefficient of about 0.378, a t-statistic of 2.68, and a p-value of 0.011, indicating that greater operational efficiency leads to higher ROA. The F-test confirms that financing risk and efficiency level simultaneously have a significant effect on profitability (F = 15.23, p < 0.001). The coefficient of determination (R² ≈ 0.62) shows that 62% of the variation in profitability is explained by the two independent variables.These findings emphasize the critical role of managing financing risk and maintaining operational efficiency in enhancing the financial performance of Islamic commercial banks in Indonesia.